2016
DOI: 10.21767/2386-5180.1000131
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Laboratory Markers for Spontaneous Bacterial Peritonitis

Abstract: Spontaneous bacterial peritonitis (SBP) is an often-lifethreatening bacterial infection in patients with liver cirrhosis with ascites. Useful laboratory methods for early diagnosis are essential. The gold standard method for the diagnosis of SBP is a polymorphonuclear leukocyte (PMN) count of ≥250 cells/mm 3 in the ascitic fluid. Some studies have investigated the usefulness of other novel laboratory methods for the diagnosis of SBP. This paper reviews studies of diagnostic markers for SBP, such as procalciton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
6
0
1
Order By: Relevance
“…As regards acute inflammatory marker C reactive protein (CRP) in serum, the current study showed a significant increase in SBP versus none SBP group. This result matched with previous results 7,9,[12][13][14][15] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As regards acute inflammatory marker C reactive protein (CRP) in serum, the current study showed a significant increase in SBP versus none SBP group. This result matched with previous results 7,9,[12][13][14][15] .…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that both CRP and ascitic fluid MIP-1β were strong independent predictors of SBP. Another study found that CRP was an independent variable in SBP prediction 12,16 while others found that CRP act as a prognostic marker in cases of cirrhotic ascites with SBP 9,14 . In this study, there was a positive correlation with total leucocyte count, serum CRP and ascitic fluid LDH in the SBP group.…”
Section: Discussionmentioning
confidence: 98%
“…high-sensitive C-reactive protein have been investigated for the diagnosis of SBP and their diagnostic usefulness is still limited and large-scale studies are needed [7].…”
Section: Figurementioning
confidence: 99%
“…Therefore, these tests may also be performed at the first paracentesis in cases of suspected spontaneous peritonitis. Biomarkers, such as procalcitonin level and leukocyte esterase reagent strips, can help diagnose SBP [20] but may not distinguish between SFP and SBP.…”
Section: Diagnosis Of Sfp and Fungiascitesmentioning
confidence: 99%